Kierunki przeobrażeń struktur organizacyjnych przedsiębiorstw przejmowanych przez inwestorów zagranicznych - Lichtarski, Janusz Marek (Transformations' directions of organizational structures of enterprises taken over by foreign investors, 2005)
In the study the author tries to identify the influence of one of globalization factors (takeovers of enterprises by foreign investors) on the shape of organizational structures of local companies. The organizational structure is viewed by five dimensions: specialization, configuration, centralization, standardization and formalization, according to the basics of the contingency approach. The text is based on literature studies and empirical research carried out in 56 enterprises from Lower Silesia.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (3); 2005; nr 1093, s. 123-135